Amanita phalloides poisoning and treatment with silibinin in the Australian Capital Territory and New South Wales. Issue 1 (21st January 2013) - Roberts, Darren M; Hall, Michael J; Falkland, Morna M; Strasser, Simone I; Buckley, Nick A
Abstract: Objectives: To report the frequency and clinical outcomes of Amanita phalloides poisoning in the Australian Capital Territory and New South Wales, and the treatments used (including silibinin). Design, setting and patients: Retrospective case series of patients admitted to public hospitals in Canberra and Sydney for suspected A. phalloides poisoning between 1999 and 2012 (identified from hospital records and calls to the New South Wales Poisons Information Centre). Main outcome measures: Frequency of poisoning and the clinical outcomes. Results: Twelve patients presented with a history suggesting A. phalloides poisoning, 10 with probable poisoning and two with possible poisoning. Eight of those with probable poisoning developed significant hepatotoxicity and four died. Silibinin was administered to nine of those with probable poisoning (the other presented before 2005). Maintaining silibinin supply became a challenge during two clusters of poisoning. Eight of the patients with probable poisoning were not long‐term residents of the ACT, and six were immigrants from Asia. Conclusions: The mortality rate due to A. phalloides poisoning in this case series was high despite treatment according to current standards, including use of silibinin, and the frequency of hepatotoxicity was more than double that for the previous decade. Ongoing public health campaigns are required.